Free software: The key to information systems in Hispano-America - Eíto-Brun, Ricardo (Anuario ThinkEPI, 2008)
Open source software is a key component in the technological development of Central and South American nations. In many cases, it is the only option that avoids the problems of the "digital divide". Strengthening the use of open source software in public administration and academic communities is a necessary step toward being able to offer quality information services to citizens. A number of interesting initiatives are highlighted in Central and South America, where free software is contributing to numerous projects that offer interesting learning opportunities.